Konsepsi Tentang Siwadalam Lontar Ganapati Tattwa (Kajian Singkat Perspektif Teologi) - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The principal doctrine of Shiva Siddhanta is that Shiva, is the supreme reality, andpersonal soul or spirit is the same essence as Shiva. In this case Shiva is depicted inthe form of foundation which is the element of Widya (element of consciousness),which is the nature that is not affected by unconsciousness and is immortal, that issturdy can not be shaken, and can not be concealed. There are three forms offoundation namely: Paramasiwatattwa, Sadasiwatattwa, and Siwatattwa. The threeTattwa is called Foundation Telu, which is the triple level of consciousness.Paramasiwatattwa has the highest awareness, Sadasiwatattwa has a moderateawareness, while Siwatattwa has the lowest consciousness.